WORK ORGANIZATION PEDIATRIC HOSPITAL IN CONDITIONS PANDEMICS OF NEW CORONAVIRUS INFECTION - Ликстанов, Михаил Исаакович; Голомидов, Александр Владимирович; Кузьменко, Светлана Анатольевна; Мозес, Вадим Гельевич; Мозес, Кира Борисовна (Mother and Baby in Kuzbass, 2021)
The article presents the basic principles of organizing inpatient pediatric care in the context of a coronavirus pandemic.
Keywords: SARS-CoV-2; COVID-19; coronavirus; pediatrics; children; planned and emergency hospitalization